Analysis of Consumer Satisfaction with Smoothie Janji Manis Products in Sumedang City Through Taste, Price and Quality Factors - Jaja, Jaja; Puspasari, Dewi; Nurtanti, Anisa Fauziah; Destania, Fany; Martiana, Novi Siti Rizki Nur; Permadi, Zahra Astri Dwi (Journal of Bussines Management Basic, 2025)
Customer satisfaction is the feeling of happiness or disappointment that arises from the comparison between expectations and the performance of the received product. Consumer satisfaction has five indicators, namely the complaint and suggestion system, customer satisfaction surveys, ghost shopping, lost customers, This research aims to identify the factors that influence consumer satisfaction with Smoothies Janji Manis products in the city of Sumedang. The type of research used is qualitative research based on post-positivism philosophy. This study uses the observation method with purposive sampling, along with interviews with the manager of Smoothies Janji Manis. This research yielded answers that the factors of taste, price, and quality significantly influence consumer satisfaction with Smoothies Janji Manis products. And consumers also agree on the large number of visitors to Smoothies Janji Manis.